Improved awareness on climate smart nutrient management options through the IOP farm in Tanzania - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
During four seasons, an experiment was run at the Farm for the Future Tanzania Ltd (FFF) which is part of Ilula Orphan Program (IOP)’s Farm, Ilula, Iringa Region, in Tanzania. The FFF farm, is training farmers in 16 villages, with a focus on dissemination activities at regional, as well as national level. The experiment showcased very effective low-emission crop fertilisation strategies that combine high maize yields with high nutrient use efficiency and low emissions.